2003
DOI: 10.1002/chin.200324107
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Investigation of Tuberculosis Inhibition Activities of Some 1,2,3‐Triazole Derivatives.

Abstract: Triazole derivativesTriazole derivatives R 0280 Synthesis and Investigation of Tuberculosis Inhibition Activities of Some 1,2,3-Triazole Derivatives. -Condensation of α-diazo-β-oxoaldehydes (I) with different amines (II) affords the title compounds in good yields. -(DABAK*, K.; SEZER, O.; AKAR, A.; ANAC, O.; Eur. J. Med. Chem. 38 (2003) 2, 215-218; Dep. Chem., Fac. Sci., Tech. Univ. Istanbul, TR-80626 Maslak, Istanbul, Turk.; Eng.) -M. Paetzel 24-107

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Compounds having S, N and O donor atoms play a vital role in antibacterial [1][2][3] , antifungal 4,5 , antitumor 6 , antitubercular 7,8 , anticancer 9 and antiviral 10 activities due to their significant biological properties. Presently, the vanadium metal chemistry is gaining attention for its remarkable activities such as antimicrobial 11 , antitumor 12 , and most recently as insulin mimetic 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Compounds having S, N and O donor atoms play a vital role in antibacterial [1][2][3] , antifungal 4,5 , antitumor 6 , antitubercular 7,8 , anticancer 9 and antiviral 10 activities due to their significant biological properties. Presently, the vanadium metal chemistry is gaining attention for its remarkable activities such as antimicrobial 11 , antitumor 12 , and most recently as insulin mimetic 13 .…”
Section: Introductionmentioning
confidence: 99%
“…They coordinate to the metal ion in many ways, depending upon the nature of the functional groups [8][9][10][11] . Studies have indicated that many triazole derived Schiff bases show antibacterial [12][13][14] , antifungal 15,16 , antimicrobial [17][18][19][20] , anticancer 21,22 , analgesic 23 , anticonvulsant 24 , antitumor [25][26][27] , antitubercular [28][29][30][31] , insecticidal, herbicidal, and plant growth regulatory [32][33][34] activities. Due to increased interest in the chemistry of vanadyl compounds and the potentially bioactive nature of triazoles, we have made an effort to combine the chemistry of vanadium(IV) with newly synthesized triazole Schiff bases L 1 -L 5 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3-Triazoles are an important class of heterocyclic compounds due to their wide range of applications as pharmaceutical agents [5,6]. The diversity of chemical structures of the 1,2,3-triazole family and their useful biological activities made these compounds attractive targets in synthetic organic chemistry and many studies have been reported on the synthesis of these compounds [7][8][9].…”
Section: Discussionmentioning
confidence: 99%